SURVEILLANCE AND SECURITY MODELS BASED ON THE ARDUINO UNO INTERFACE - Zakariashvili, M. Z.; Sivsivadze, G.; Chidrashvili, M.; Khechoshvili, L. (Automatizácia tehnologičeskih i biznes-processov, 2023)
The issue demonstrated in the article covers construction of   surveillance and security systems on Arduino UNO platform Technological and Software aspect which are based on Quality Semiconductor Sensor-MQ135; PIR Motion Sensor and use of blocking peculiarities. The project model integration process in both a virtual and physical context is described in detail and analyzed in the paper. The following are specifically used: An Arduino UNO microcontroller board, the Arduino Software IDE (Integrated Development Environment), a local code editor on the PC, and the virtual online platform tinkercad.com. The work is supplemented by pertinent electronic diagrams, schemes, software code, descriptions of fundamental functionalities, links to virtual project simulation, real-world application, and links to video recordings of the experiment in order to demonstrate the project model's smooth operation.